The role of interleukin-6 in stress-induced hyperthermia and emotional behaviour in mice - Butterweck, Veronika; Prinz, Simone; Schwaninger, Markus (Behavioural brain research, 2003)
Psychological stress influences behaviour as well as autonomic functions such as body temperature. The mechanism that induces hyperthermia during stress is unknown. A recent hypothesis suggests that interleukin-6 (IL-6), an endogenous pyrogen, elevates body temperature during stress. To investigate the role of IL-6 during stress, we measured mRNA levels of IL-6 by quantitative PCR in various tissues 60min after exposure of mice to open field stress. IL-6 mRNA was elevated in the hypothalamus three-fold and in the pituitary two-fold. However, there was no difference between the increase in body temperature after exposure to 60min open field stress in wild-type controls (35.2±0.6-37.3±0.5°C) and IL-6-deficient animals (34.8±0.4-37.0±0.3°C). In contrast to body temperature, emotional behaviour differed between wild-type controls and IL-6-deficient mice. IL-6-deficient animals showed higher locomotor activity in an open field and lower levels of exploration of the open arms of the elevated plus maze than control animals. These data suggest that IL-6 plays an important role in the control of emotionality, but not in the regulation of body temperature after psychological stress.
Gesehen am 22.03.2021